The relationship between work motivation, work environment, and work output of health workers at the Bandar Khalifah Deliserdang Health Center - Naibaho, Togar; Naibaho, Winfrontstein (Institute of Computer Science (IOCS), 2025)
The purpose of this study was to determine the relationship between work motivation and organizational culture on the performance of the Bandar Khalifah Health Center, Deliserdang Regency. The implication of this study is to be able to improve the ability of a leader and the existing organizational culture, so that aspects of employee job satisfaction can be met, because in general high employee job satisfaction will be able to increase the work motivation of the Bandar Khalifah Health Center staff, Deliserdang Regency. The performance of health workers is a critical factor in ensuring the delivery of effective and quality health services, especially at the primary healthcare level such as community health centers (Puskesmas). In Indonesia, Puskesmas serve as the frontline for promoting, preventing, and treating public health issues. The Bandar Khalifah Deliserdang Health Center is one such facility that plays an essential role in addressing the health needs of the local community. However, the quality of services provided is often influenced by internal factors, including work motivation and the work environment. Motivation drives employees to perform their duties diligently and achieve institutional goals, while the work environment—encompassing physical conditions, organizational culture, and interpersonal relationships—affects job satisfaction and overall productivity.